From the 1986 Annual Conference - CAML Editor, (CAML Review / Revue de l'ACBM, 1986)
Folklore Session summaryMusic therapy Session summaryAn annotated checklist of separately issued bibliographies and discographies of Music therapy and Psychology of music - C. Gérald Parker